The effects of the image attributes of golf star athletes supported by adult amateur golfers on sports participation desire and continuation intention - Yang, Ji-Hye; Kim, Ga Young; Yang, Hye Jin; Choi, Chulhwan; Bum, Chul-Ho (Frontiers in Psychology, 2025)
The image attributes of sports star athletes demonstrate positive effects on sports fans' psychological factors. In the context of golf, fans are also influenced by the players they support, experiencing a range of emotions. Therefore, this study aimed to examine the effects of the image attributes of golf star athletes—supported by adult amateur golfers—on the desire for sports participation and the intention to continue. This study involved 356 adult amateur golfers in Korea (253 male, 103 female). Questionnaires were used to measure participants' perceptions of image attributes, their desire for sports participation, and their intention to continue participating in the sport. The data were analyzed using descriptive statistics, validity and reliability, and multiple regression analyses. First, the image attributes factors (physical appearance, performance ability, and moral image) all had a significant effect on both the desire for sports participation and the intention to continue participating in the sport. However, performance ability did not impact affective desire. Second, while cognitive and behavioral desires significantly influenced the intention to continue participating, affective desire did not have an effect. In conclusion, fans identify diverse athletes' images (e.g., physical appearance, performance, and personality) through attending or watching sports games, and positive sports star image attributes enhance sports fandom, participation desire, and continuation intention. The results of this study indicate a close relationship between golf fans' perceptions of players' image attributes and their psychological factors. These findings could help improve fans' quality of life and provide valuable insights for understanding their fandom.